Semiconductor properties of nanostructured Al doped ZnO thin film annealed at different temperatures: article / Muhammad Amin Baseer - Baseer, Muhammad Amin (2014)
The semiconductor properties of nanostructured aluminum (Al) doped zinc oxide (ZnO) thin film. This project has been focused on semiconductor properties that consist of electrical, optical and structural properties of Al doped ZnO thin film. The effects of annealing temperatures of Al doped Zno thin film properties have been investigated. This project consist of three processes which are thin film preparation, deposition and characterization. The thin films were characterized using 2 probe Current-Voltage (I-V) measurement and UV-Vis-NIR spectrophotometer for electrical properties and optical properties respectively. The surface morphology has been characterized using field emission scanning electron microscope (FESEM). The I-V measurement result indicated electrical properties of Al doped ZnO thin film improved with increased of annealing temperature. The absorption coefficient spectra obtained from UV-Vis-NIR spectrophotometer measurement show all films have low absorbance in visible and near infrared (IR) region but have high UV absorption properties. The calculated Urbach energy indicated the defects concentrations in the thin films increase with doping concentrations The FESEM investigations shows that the grain size becomes increase when the annealing temperature increase.